Exploring the Creative Writing Strategies of English Major Students - Fuentes, Mark Dennis; Agbon, Eumar Jess (International Journal of Sustainability and Advanced Integrated Research, 2026)
Creative Writing fosters academic success in developing essential skills and intellectual growth. This study investigates the role of writing strategies on improving the creative writing skills among English major students. A focus on grammar and structure in academic settings can sometimes hinder the flow of creativity and self-expression in writing. This Qualitative Phenomenological study examines the impact of constructive criticism on the writing skills of English major students in Davao del Sur State College. Through qualitative interviews with ten participants, the study investigates the role of writing strategies, constructive criticism, and proofreading that students experience during their writing. The study reveals that constructive feedback significantly impacts students’ strategies in creative writing by also fostering proofreading and simplifying words usage. On the other hand, the fear of judgement, and language capabilities may hinder the students’ participation, and limiting the variety of perspectives. The findings of this study highlighted the importance of providing structured and organize constructive feedback among students written outputs, and incorporate proofreading, and engaging students in writing workshops to enhance and develop their writing skills and overall learning experience.
Keywords: Writing Difficulties, Creative Writing, Constructive Feedback, Writing Strategies